Model and Method for Multiobjective Time-Dependent Hazardous Material Transportation. (14th December 2014) - Zhou, Zhen; Che, Ada; Chu, Feng; Chu, Chengbin
Abstract : In most of the hazardous material transportation problems, risk factors are assumed to be constant, which ignores the fact that they can vary with time throughout the day. In this paper, we deal with a novel time-dependent hazardous material transportation problem via lane reservation, in which the dynamic nature of transportation risk in the real-life traffic environment is taken into account. We first develop a multiobjective mixed integer programming (MIP) model with two conflicting objectives: minimizing the impact on the normal traffic resulting from lane reservation and minimizing the total transportation risk. We then present a cut-and-solve based ε -constraint method to solve this model. Computational results indicate that our method outperforms the ε -constraint method based on optimization software package CPLEX.